MANAJEMEN OPDM (ORGANISASI PELAJAR DAYAH AL-MUSLIMUN) DALAM MENGEMBANGKAN BAKAT TTQ (TAHFIZ TASMI’ ALQURAN) (Studi Kasus di Dayah Terpadu Al-Muslimun Lhoksukon) - Wahyuni, Suci (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2020)
This research was conducted to find out how about the planning, implementation and evaluation in developing Tahfiz Tasmi' Alquran skills in Islamic boording school of Al-Muslimun Lhoksukon. Data analysis was done by reducing data, presenting data and drawing conclusion on the data that had been collected. While to guarantee on the validity of the data, triangulation techniques were used. The results of this research indicated that: first, the planning students organazation of Al-Muslimun boording school in developing Tahfiz Tasmi' Alquran skills consists of several stages: (1) determination of goals and objectives; (2) the implementation; (3) periodization development; (4) identification of supporting factors and inhibiting factors (5) methods in developing Tahfiz Tasmi' Alquran skills, covering the Tasmi' method, Qira'ah fi al-shalah method and lectures method. Second, the implementation students organazation of Al-Muslimun boording school in developing Tahfiz Tasmi' Alquran skills could also be seen by the presence of several elements, they are: (1) material guidance; (2) communication; (3) motivation; (4) maintenance; and (5) development in the implementation of this Tahfiz Tasmi' Alquran. Third, evaluation students organazation of Al-Muslimun boording school in developing Tahfiz Tasmi' Alquran skills could be seen by the evaluation of the learning process that was carried out every day and evaluation of learning outcomes that were carried out every semester.